Analisis Pengaruh Efektivitas Kerja dan Motivasi terhadap Kinerja Mahasiswa Magang pada Sistem Work From Home: Studi Kasus di Yayasan Bakti Milenial - Jenny Nurani Hutasoit; Anita Christine Sembiring (Politeknik Kampar, 2025)
This study aims to analyze the influence of the Work From Home (WFH) system and work motivation on the performance of internship students at the Bakti Milenial Foundation. The background of this research lies in the shift of work patterns during the pandemic era, where many organizations and institutions implemented remote work systems, including internship programs. This shift is expected to affect the way students carry out their tasks, adapt to technological facilities, and manage work discipline. In addition, motivation is considered an important internal factor that drives students to work more effectively and productively, regardless of the working system applied. This research adopts a quantitative approach with an explanatory research method to test the causal relationship between variables. The population of this study includes all internship students at the Bakti Milenial Foundation, while the sample was selected using a snowball sampling technique involving 30 respondents. Data collection was carried out using questionnaires distributed online through Google Forms. The collected data were then analyzed statistically to determine the extent of the effect of the independent variables, namely WFH and work motivation, on the dependent variable, namely student performance. The results of this study reveal two main findings: (1) The Work From Home system has no positive and significant effect on the performance of internship students at the Bakti Milenial Foundation. This finding suggests that the flexibility of remote work does not automatically improve student performance, possibly due to limitations in supervision, communication barriers, or challenges in maintaining focus. (2) Work motivation has a positive and significant effect on the performance of internship students. This indicates that intrinsic and extrinsic motivation play a crucial role in driving students to complete their tasks effectively and responsibly.